URACHUS: A LITERATURE REVIEW - Zahri A. Rani; Said A. Khalilullah, Reza Maulana (CV. ADIBA AISHA AMIRA, 2023)
Urachal anomalies generally do not have significant morbidity and mortality. Without other serious congenital anomalies, the prognosis for urachal anomalies is good, except in cases of adenocarcinoma where the prognosis is poor. However, if a serious congenital anomaly is found along with urachal remnants, the prognosis is poor. Patients with surgically treated urachal remnants generally have a good condition and quick recovery. Complications of urachal remnants such as adenocarcinoma have a poor prognosis